Basin with Multiple Sediment Sources: Tectonic Evolution, Stratigraphic Record and Reservoir Potential of the Bunguran Trough, South China Sea - John Jong; Steven M. Barker; Franz L. Kessler; Tran Quoc Tan (Ikatan Ahli Geologi Indonesia, 2017)
The Bunguran Trough is an intra-continental pull-apart basin located in the deepwater domain of the Rajang/West Luconia Delta province, offshore Sarawak. The area evolved as a tectonically-induced sag basin, where the two major lineaments, the Baram Line and the Red River Fault, appear to coalesce to form a major releasing fault bend. Its oldest stratigraphy was formed by shelf clastic deposits of the Late Oligocene Cycle I, Gabus Formation of the Natuna Basin, now buried to a depth of more than 7,000m. The Neogene clastics deposited above are of neritic and bathyal characters. The Early Miocene Cycles II/III, Arang Formation equivalent, consist of shallow marine to slope deposits, and are overlain by base-of-slope to very distal muddy sediments equivalent to Cycle IV and younger Terumbu and Muda formations. All sedimentary units, apart from the youngest Holocene section were subjected to deformation by a variety of tectonic drivers at distinct intervals.Investigation of the Late Oligocene to present-day palaeogeographic evolution of the Natuna and offshore Sarawak regions, in conjunction with a study of the Plio-Pleistocene deformation history and the corresponding sedimentation rates in the Bunguran Trough reveal the following sediment source patterns:The Natuna contributed medium to mostly fine-grained feldspatic and quartz-rich turbidite deposits.Fine sand and silt-rich deposits reached the Bunguran Trough from the fringes of the Rajang (or West Luconia) Delta. The advancing delta front generated turbidite currents running dominantly north to northeast. These clastics can be characterised as mud-rich, with channelised, and highly sinuous geometries accompanied with lobate turbidite deposits having higher sand potential.A minor amount of sediment might have been derived from localised sources in the Dangerous Grounds/North Luconia and Central Luconia Platform areas to the north and east, respectively.From Oligocene to Early Miocene times, sediments were probably sourced from the Natuna Arch/Terumbu Platform areas, but during the Neogene sediment supply shifted to the Rajang Delta in the south. In the Pliocene the Natuna area became important again, as demonstrated by mineralogy and recently acquired 2D/3D seismic data. In addition, the semi-quantitative analysis of the sedimentation rates showed that the rates were low before 3Ma, increasing in the Late Pliocene, and peaking in the Pleistocene. Physical compaction is thought to have played a key role in this trend, in addition to the increased sediment supply from the Natuna Arch.This sequence stratigraphic and sediment compositional study suggests that the Late Miocene to Pleistocene (post-Mid Miocene Unconformity) intervals of the Bunguran Trough consist of predominantly deepwater slope to basinal deposits including turbidites, mass transport deposits, gravity flows and hemipelagic mudstones. Recent exploration well results suggest that sediment provenance from the Natuna Arch provided siltier material with some calcareous content, while the Rajang Delta provided very fine-grained material with very little sand. The quality and distribution of reservoir sand remain the main exploration risk in the Bunguran Trough, largely due to the fine-grained argillaceous nature of the predominant Rajang Delta source.